Intracranial ependymoma and its appearance on CT Scan. - Arif Faisal Arif Faisal (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
Intracranial ependymoma is an uncommon central nervous system neoplasms which happens in all age groups but has higher incidence occurring in the posterior fossa in infants and children. The location of the tumor is in the ventricle system, especially the fourth ventricle. Depending on its position to tentorium, the tumors can be divided into supratentorial and infratentorial. Hydrocephalus and calcifications usually occur in both types of tumors. Ependymomas have unspecific and varied appearance in density on computed tomography examination, but most of them are isodense. The supratentorial ependymoma tends to be hypodense, cystic-like lesion and enhanced (homogenous and nonhomogenous) after contrast, injection. The Infratentorial ependymoma are mostly hypodense and similar enhancement to supratentorial tumor. Treatments consist of surgical resection and radiotherapy, but the overall results are not very effective.Keywords : ependymoma - infratentorial tumor - supratentorial tumor - contrast enhancement